An enzyme-responsive and NIR-triggered lipid–polymer hybrid nanoplatform for synergistic photothermal/chemo cancer therapy. (6th April 2022) - Tang, Lu; Xiao, Qiaqia; Yin, Yue; Mei, Yijun; Li, Jing; Xu, Lin; Gao, Hongbin; Wang, Wei
Abstract : A lipid–polymer hybrid nanosystem that co-loaded indocyanine green (ICG) and dichloroacetate (DCA) for combined anti-cancer photothermal/chemotherapy. Abstract : A combination of photothermal therapy (PTT) and chemotherapy is an emerging therapeutic strategy with promising clinical prospects in cancer treatment. Despite the huge progress achieved in the past years, a number of obstacles still hamper the therapeutic efficacy of this synergistic modality such as uneven heat distribution, lack of targetability of anti-cancer agents and dosage-related side effects. Thus, developing a nanoplatform for targeted drug delivery against cancer is of great necessity. Herein, a lipid–polymer hybrid nanosystem (LP/ID) based on polyethyleneimine (PEI)-lecithin-polyethylene glycol (PEG) was fabricated to co-load indocyanine green (ICG) and dichloroacetate (DCA) for combined photothermal/chemotherapy. DCA and ICG were linked to the PEI backbone to form a dense hydrophobic core through amide bonds and electrostatic interactions, which increased the payload of DCA and ICG as well as achieved enzyme-responsive drug release because of the overexpressed amidase in tumor cells. Lecithin and DSPE-PEG2000 self-assembled around the hydrophobic complexes to obtain prolonged blood circulation and attenuated systemic toxicity of the hybrid nanosystem. The prepared LP/ID exhibited favourable stability in a physiological environment, good tumor imaging properties, and satisfactory photothermal/chemotherapeutic performance. Moreover, LP/ID could also enhance the cellular uptake and tumor retention capacity in comparison with free drug administration. Notably, by co-loading two therapeutic agents with different anti-cancer mechanisms, an obvious inhibitory effect on tumor growth was observed with negligible damage to normal tissues and organs because of the synergistic photothermal/chemotherapy effect, indicating the great potential of LP/ID as a robust nanoplatform for cancer treatment.